Relasi Antara Efisiensi Operasional Dan Profitabilitas - Sri Wahyuni Jamal; Fenty Fauziah; Azhar Latief; Muh. Najeri Al Syahrin (Universitas Serang Raya, 2022)
The relationship between operational efficiency and profitability cannot be ignored because increasing profitability is necessary for the long-term survival of any company. Efficiency can be measured through several financial ratios using working capital turnover and total asset turnover. Then for profitability using return on assets. The sample of companies used is the coal mining sector as many as 10 companies for 3 years from 2017-2019. Multiple linear regression is used to describe the dynamics of changes in return on assets. Based on the results of the analysis, we found that either partially or simultaneously working capital turnover and total asset turnover have a significant effect on return on assets.